Look before you LEAPP™: An interprofessional approach to bedside pediatric inpatient procedures. Issue 1 (27th September 2013) - Botash, Ann S; Jeski, Michelle; Baish Cameron, Colleen; K. Nelsen, Elizabeth; Haines, Pamela; Bennett, Nicholas
Abstract: The Golisano Children's Hospital at Upstate Medical University is a 71 bed children's hospital within a hospital, serving nearly two million people in Central New York. Minor procedures occur daily in all children's hospitals, yet team coordination when planning for these procedures is often overlooked. LEAPP™ is a mnemonic for: Listen, Evaluate, Anticipate, Plan, and Proceed. The "Look before You LEAPP™" program was developed by a group of nurses, child life specialists, faculty, a chief resident and a fellow. LEAPP™ is a team-based program providing consistent care to all children undergoing inpatient procedures. It improves patient satisfaction and reduces procedural distress. Through LEAPP™ steps, teams are created at point of care — at the bedside or treatment room of inpatient units. Educational goals are linked to the practical goal of cooperation for good health care. The approach uses an online educational module for residents, students and nurses to introduce an innovative protocol and a planning tool.1 Pocket cards, promotional pens, and logo door-clings, purchased through grant funds (The Foundation for Upstate Medical University) were initially used to encourage participation. Pre/post observations of procedural planning and performance of the nurse, caregiver, physician, child-life specialist and independent observer included patient and family preparation, pain and anxiety, staffing and supplies, and satisfaction. Fifty procedures were assessed pre-implementation and 28 post implementation. Although satisfaction with procedures improved between pre and post LEAPP™ implementation, there were overall differences in satisfaction with procedural management and pain/anxiety control by physicians, caregivers, and staff that remained statistically significant. Interdisciplinary bedside teamwork can be used to support interprofessional education and this education can similarly be used to support improved patient outcomes.